Desarrollo industrial y sector externo : Propuesta de un criterio de evaluación y de una metodología para determinar una estrategia de sustitución de importaciones - Aldabe, Hernán (1966)
This is a problem of macroeconomic decision concerning the assignment of resources in purely economic objectives. Once the field of the subject is axiologically delimited, the author analyses all possible pattern to point out the maximum of its efficiency showing the concept of added value as a measure of the social utility of assignations. The problem thus stated, proposed to make use of the lineal programmation as a method for planning and resolving problems bringing out the versatility of this technique when considering a large variety of situation and restrictions. Then, he takes into account the possibility of remarking the limits of validity in the initial solution when it faces changes in problem data by means of alteration of restrictions. The author examines the virtue of lineal programmation, that of enhancing the boundaries of "best" thought modification of the added values, making thus possible the measurement of future political influences on prices. Finally he states that quantitative solutions must always be taken as suggestions which only show a region of possible combinations, and that the final decision must emerge once all the social and political imponderable have been considered verifying if the solution of the problem fits the meta-economic values.